Xpert MTB/RIF assay for the diagnosis of extrapulmonary tuberculosis: a diagnostic evaluation study. (August 2019) - Tadesse, M.; Abebe, G.; Bekele, A.; Bezabih, M.; Yilma, D.; Apers, L.; de Jong, B.C.; Rigouts, L.
Abstract: Objectives: The diagnosis of extrapulmonary tuberculosis (EPTB) is often made on clinical suspicion alone, resulting in both under- and overdiagnosis and relatively poor outcomes. In this study, we evaluated the clinical utility of the Xpert MTB/RIF on routinely collected extrapulmonary specimens in Ethiopia. Methods: This study was carried out at Jimma University Specialized Hospital, Southwest Ethiopia. Extrapulmonary specimens were collected from 572 patients clinically suspected of suffering from EPTB. All specimens were tested for TB by smear microscopy, culture, and Xpert MTB/RIF. The diagnostic accuracy of Xpert MTB/RIF was calculated and compared to a composite reference standard (CRS), comprising clinical and laboratory results. Results: In total, 572 extrapulmonary specimens (279 lymph node, 159 pleural, 80 peritoneal, 45 cerebrospinal, and nine pericardial fluids) were tested. The pooled sensitivity and specificity of Xpert MTB/RIF were calculated to be 75% (95% CI 70–80) and 98% (95% CI 97–100) respectively when compared to the CRS. The highest sensitivity was documented for lymph node specimens (90%; 95% CI 86–94), moderate sensitivity for cerebrospinal fluid (53%; 95% CI 28–79), while the sensitivity was lowest for pleural (30%; 95% CI 17–44) and peritoneal (32%; 95% CI 12–51) fluids. Xpert MTB/RIF in addition detected rifampicin resistance in 13 patients, in perfect agreement with results from the line probe assay. Conclusions: Xpert MTB/RIF may be used as initial diagnostic tool for testing of lymph node specimens from patients suspected of having TB lymphadenitis. The added value of Xpert MTB/RIF to diagnose pleural or peritoneal TB is limited by its poor sensitivity.